An EFG-SBM based partitioning algorithm for two-dimensional elastic analysis of cyclically symmetrical structures. Issue 2 (20th April 2015) - Guo, Xiaofeng; He, Yiqian; Yang, Haitian
Abstract : Purpose: – The purpose of this paper is to exploit the cyclic symmetry to reduce the computational expense of scaled boundary method (SBM) which may cumber its further application. Design/methodology/approach: – A partitioning EFG-SB (Element-free Galerkin-SB) algorithm is proposed for the two-dimensional elastic analysis of cyclically symmetric structures. Findings: – By utilizing the cyclic symmetry and partitioning algorithm, the whole computational cost can be significantly reduced. Three numerical examples are given to illustrate the advantages of the proposed algorithm. Originality/value: – It is proved that the matrices of eigenvalue and system equations of EFG-SBM for cyclically symmetric structures are block-circulant so long as a kind of symmetry-adapted reference coordinate system is adopted. No matter whether displacement constraints are cyclically symmetric or not, the partition is available for the eigenvalue equations. Therefore the major computational cost can be saved via the proposed partitioning algorithm. This paper provides an efficient algorithm for the two-dimensional elastic analysis of cyclically symmetric structures using EFG-SBM. A higher computing efficiency can be expected since the proposed partitioning algorithm facilitates parallel processing.